Studies in Zebrafish and Rat Models Support Dual Blockade of EP2 and EP4 (Prostaglandin E2 Receptors Type 2 and 4) for Renoprotection in Glomerular Hyperfiltration and Albuminuria. Issue 4 (30th January 2023) - Kourpa, Aikaterini; Schulz, Angela; Mangelsen, Eva; Kaiser-Graf, Debora; Koppers, Nils; Stoll, Monika; Rothe, Michael; Bader, Michael; Purfürst, Bettina; Kunz, Severine; Gladytz, Thomas; Niendorf, Thoralf; et al.
Abstract : Background: Glomerular hyperfiltration (GH) is an important mechanism in the development of albuminuria in hypertension. Upregulation of COX2 (cyclooxygenase 2) and prostaglandin E2 (PGE2 ) was linked to podocyte damage in GH. We explored the potential renoprotective effects of either separate or combined pharmacological blockade of EP2 (PGE2 receptor type 2) and EP4 (PGE2 receptor type 4) in GH. Methods: We conducted in vivo studies in a transgenic zebrafish model ( Tg[fabp10a:gc-EGFP] ) suitable for analysis of glomerular filtration barrier function and a genetic rat model with GH, albuminuria, and upregulation of PGE2 . Similar pharmacological interventions and primary outcome analysis on albuminuria phenotype development were conducted in both model systems. Results: Stimulation of zebrafish embryos with PGE2 induced an albuminuria-like phenotype, thus mimicking the suggested PGE2 effects on glomerular filtration barrier dysfunction. Both separate and combined blockade of EP2 and EP4 reduced albuminuria phenotypes in zebrafish and rat models. A significant correlation between albuminuria and podocyte damage in electron microscopy imaging was identified in the rat model. Dual blockade of both receptors showed a pronounced synergistic suppression of albuminuria. Importantly, this occurred without changes in arterial blood pressure, glomerular filtration rate, or tissue oxygenation in magnetic resonance imaging, while RNA sequencing analysis implicated a potential role of circadian clock genes. Conclusions: Our findings confirm a role of PGE2 in the development of albuminuria in GH and support the renoprotective potential of combined pharmacological blockade of EP2 and EP4 receptors. These data support further translational research to explore this therapeutic option and a possible role of circadian clock genes.